Research on temperature composite control system for radioactive waste incineration equipment - Zhiyong Wang; Yao Cui; Jing Ma; Bo Zhang; Liudong Hou; Haili Li (International Journal of Advanced Nuclear Reactor Design and Technology, 2025)
This paper presents a multi-mode control scheme for the temperature regulation of radioactive waste incineration equipment, integrating modern and fuzzy control theories. Separate controllers were designed for the preheating and operating stages. In preheating phase, a mathematical model was developed using mechanism modeling, enabling automatic control through sequential and proportional-integral-derivative control. For operation phase, a composite control approach combining fuzzy control and special variable ratio control was proposed. The fuzzy controller used temperature difference, changing rate and acceleration as inputs, adjusting oxygen concentration to regulate combustion temperature. Experimental results demonstrated 27 h of stable automatic control with a maximum temperature deviation of 9.1 °C and an error rate of 1.65 %. The proposed scheme provides specific control strategies with quantifiable performance indicators, proving its effectiveness in maintaining temperature stability in radioactive waste incineration.